Kontroversi Status Hukum Nikah Mut'ah (Analisis terhadap Pendapat Para Ulama) - May, Asmal (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
There  are  two  issues  that  always  actual  in  Islamic Marriage/Family Law (Munakahat), which until now  has always discussed by scholars, because no matter how much people need a  clear  legal  status,  ie  Marriage  Mut'ah  and  Sirri.  Such controversies are appropriately addressed with no preconceived notions, so that it can be studied with a critical attitude and well mannered  (no  blasphemy).  Marriage  mut'ah  a  variant  in  which marriage  is  governed  by  the  contested  legitimacy  of  Islam between  Sunnis  and  Shi'ites.  In  general,  the  Sunnis  consider mut'ah  marriage  is  a  type  of  marriage  is  not  legitimate  or illegitimate based on the testimony of hadith, Umar ibn Khattab fatwa and ijma 'Sunni clerics. As for the Shiites, particularly the Shiite  Istna  'Ash'arite,  consider  mut'ah  marriage  is  allowed  or lawful, although in practice  they  diffe r  on  some  of  the implementation.  This  paper  presents  the  analysis  about  the formulation of opinions about the scholars on the legal status of marriage mut'ah.